2016
DOI: 10.1111/jocd.12222
|View full text |Cite
|
Sign up to set email alerts
|

Safety and patient subjective efficacy of using galvanopuncture for the treatment of striae distensae

Abstract: The use of galvanopuncture for the treatment of striae alba demonstrated a significant improvement in the lesions with visible results. This study supports the high degree of patient's satisfaction and demonstrate the safe and effective use of galvanopuncture in the treatment of striae alba on several skin types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…4 The therapeutic modalities from the previous study include topical agents, chemical peeling, microdermabrasion, radiofrequency, fractional lasers, diode laser, intense pulse light, percutaneous collagen induction therapy, platelet-rich plasma, infrared light, intense focused ultrasound, biostimulating filler injection, and galvanopuncture. 4,10,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Lasers and energy-based devices are considered non-invasive treatments that successfully stimulate new collagen and elastin production and defeat SD pathogenesis. However, results can be challenging with long downtime and a higher risk of post-inflammatory hyperpigmentation (PIH).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The therapeutic modalities from the previous study include topical agents, chemical peeling, microdermabrasion, radiofrequency, fractional lasers, diode laser, intense pulse light, percutaneous collagen induction therapy, platelet-rich plasma, infrared light, intense focused ultrasound, biostimulating filler injection, and galvanopuncture. 4,10,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Lasers and energy-based devices are considered non-invasive treatments that successfully stimulate new collagen and elastin production and defeat SD pathogenesis. However, results can be challenging with long downtime and a higher risk of post-inflammatory hyperpigmentation (PIH).…”
Section: Discussionmentioning
confidence: 99%
“…Most SD treatments therapeutically target to increase collagen production, reduce erythema, or increase pigmentation 4 . The therapeutic modalities from the previous study include topical agents, chemical peeling, microdermabrasion, radiofrequency, fractional lasers, diode laser, intense pulse light, percutaneous collagen induction therapy, platelet‐rich plasma, infrared light, intense focused ultrasound, biostimulating filler injection, and galvanopuncture 4,10,21–36 . Lasers and energy‐based devices are considered non‐invasive treatments that successfully stimulate new collagen and elastin production and defeat SD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The observed results include angiogenesis, cellular proliferation, and the reconfiguration of collagen bundles. Subjects with darker skin had the most favorable result, often associated with the most challenging skin type [95] .…”
Section: Galvanopuncturementioning
confidence: 99%
“…In this therapy low level direct micro current is applied to the body with the help of needles to reduce the oxidative injury with subsequent collagen production. Its use in SA was investigated by Bitencourt[89] et al which demonstrated substantial clinical improvements in 32 SD patients after 10 sessions. Ferreira et al [90] has compared galvanopuncture versus dermabrasion; he found both treatments showed improvement in SD but the difference was statistically insignificant.…”
Section: Miscellaneous Light Based Therapies (Other Than Lasers) For Sdmentioning
confidence: 99%